English Language Teaching Practice in Elementary School Under the Merdeka Curriculum - Efendi, Tri Achmad; Fajar Prihantini, Apsari (Journal of Applied Linguistics and English Education, 2025)
English has been an important foreign language in Indonesia; it is taught since students in early age. This paper is aimed at portraying the implementation of teaching English in elementary schools in Surabaya which focuses on figuring out typical method, strategies and activities used in elementary English classroom. In addition, this study would like to find out the teachers’ beliefs in teaching English in elementary school. To answer the research questions, the study employed qualitative methods with questionnaire as the instrument. There were 13 participants involved in this study. The questionnaire was categorized in two main topics; teaching activities and teacher’s beliefs in English teaching. The result of the current study found out that mostly teachers used games in their teaching activities. Also, they believed that.